Emotions Toward Sustainable Innovations: A Matter of Value Congruence - Contzen, Nadja; Perlaviciute, Goda; Sadat-Razavi, Pantea; Steg, Linda (Frontiers in Psychology, 2021)
Public resistance to sustainable innovations is oftentimes accompanied by strong negative emotions. Therefore, it is essential to better understand the underlying factors of emotions towards sustainable innovations to facilitate their successful implementation. Based on the Value-Innovation-Congruence model of Emotional responses (VICE model), we argue that positive and negative emotions towards innovations reflect whether innovations are congruent or incongruent with (i.e., support or threaten) people’s core values. We tested our reasoning in two experimental studies (N = 114 and N = 246), by asking participants to evaluate innovations whose characteristics were either congruent or incongruent with egoistic values (study 1) or with biospheric values (study 1 and study 2). In line with the VICE model, we found overall that the more an innovation was perceived to have characteristics congruent with these values, and biospheric values in particular, the stronger positive and the weaker negative emotions they experienced towards the innovation, especially the more strongly people endorsed these values. Emotions, in turn, were related with acceptability of innovations. Our findings highlight that emotions towards innovations can have a systematic basis in people’s values that can be addressed to ensure responsible decision-making on sustainable innovations.